Increasing multicultural understanding - Locke, Don C.; Bailey, Deryl F.; Sage eBooks ([Los Angeles] : SAGE, 2016)
This edition of 'Increasing Multicultural Understanding' has been revised and updated. Locke presents a model which helps counsellors understand culturally different groups and the role culture plays in shaping the way people think, feel and act.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 20, 2016).
Keywords: Cultural pluralism -- United States; Minorities -- United States; United States -- Ethnic relations; United States -- Race relations; Electronic books